Extremely Foldable and Highly Transparent Nanofiber-Based Electrodes for Liquid Crystal Smart Devices - In Chul Kim (Nature Portfolio, 2018)
Abstract The nylon 6 nanofiber-reinforced cellulose acetate (NF-r-CA) film as a fiber-based transparent substrate is used to develop the highly transparent electrodes with excellent durable and extremely foldable properties. Mechanical properties of the NF-r-CA films are greatly improved, suggesting that the nanofibers provide an effective reinforcement. The NF-r-CA transparent films show smooth surface morphologies (RRMS ~ 27 nm) than as-spun nylon 6 nanofiber membrane, indicating the successful infiltration of cellulose acetate into the voids of nylon nanofiber membranes. The NF45-r-CA electrodes prepared using AgNWs concentration of 0.025 wt% and electrospinning time of 45 min are highly transparent (~90%), lower sheet resistance (~24 Ω sq−1) and mechanically robust (59.7 MPa). The sheet resistance of NF45-r-CA electrodes remains almost constant, and the change ratio is less than 0.01% even after a repeated bending test of 10,000 cycles (bending radius ~1 mm), whereas ITO electrode shows gradual increase in sheet resistance and then eventually no electrical signal at about 270 cycles. We also demonstrate the successful fabrication of the foldable polymer-disperse liquid crystal film utilizing highly transparent NF45-r-CA electrode, which shows outstanding working stability after bending test of 500 cycles at an extreme bending radius of 1.5 mm.